2011
DOI: 10.1039/c1ob05478c
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and evaluation of nitric oxide releasing derivatives of 3-n-butylphthalide as antiplatelet and antithrombotic agents

Abstract: Novel nitric oxide (NO) releasing derivatives (7a-7l) of 3-n-butylphthalide (NBP) were designed and synthesized. Compound 7e inhibited the adenosine diphosphate (ADP), thrombin (TH) and arachidonic acid (AA)-induced in vitro platelet aggregation, superior to NBP and aspirin, released moderate levels of NO, and improved aqueous solubility relative to NBP. Furthermore, 7e exhibited greater antithrombotic activity than NBP and aspirin in rats, and protected against collagen and adrenaline-induced thrombosis in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…7). NBP possesses a multiplicity of important biological properties, including anti-inflammatory [12], anti-apoptotic [3,7], anti-platelet and anti-thrombotic [13], and antioxidative [10,11] properties. These attributes, acting alone or in unison, confer effective neuroprotection in a variety of brain injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). NBP possesses a multiplicity of important biological properties, including anti-inflammatory [12], anti-apoptotic [3,7], anti-platelet and anti-thrombotic [13], and antioxidative [10,11] properties. These attributes, acting alone or in unison, confer effective neuroprotection in a variety of brain injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In cellular model of Parkinson's disease, NBP reduced mitochondrial dysfunction and oxidative damage [10], and death of dopaminergic neurons [11]. It was suggested that these neuroprotective effects of NBP were mediated by its anti-inflammatory [12], anti-apoptotic [3,7], anti-platelet and anti-thrombotic [13], and anti-oxidative [10,11] properties. NBP was approved by the State Food and Drug Administration of China for clinical use in ischemic stroke patients in 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Its molecular structure was shown in previous studies [9, 29] and was dissolved in normal saline. Membrane and cytosol protein extraction kit and Lactate dehydrogenase (LDH) kit were obtained from Beyotime Institute of Biotechnology (Haimen, China).…”
Section: Methodsmentioning
confidence: 99%
“…1) as potent anti-ischemic stroke agents which showed excellent antiplatelet and antithrombotic activities. 11,12 In the present study, to obtain new agents with stronger potency, we employed 1 as the lead compound to design and synthesize a novel class of NO-releasing derivatives (10a-l, Fig. 2).…”
mentioning
confidence: 99%